1975
DOI: 10.1136/bmj.3.5975.67
|View full text |Cite
|
Sign up to set email alerts
|

Growth hormone release inhibiting hormone: actions on thyrotrophin and prolactin secretion after thyrotrophinreleasing hormone.

Abstract: SummaryThe hypothalamic tetradecapeptide growth hormone release inhibiting hormone (GH-RIH) blocked the thyrotrophin response to thyrotrophin-releasing hormone (TRH) in normal people and in patients with primary hypothyroidism. This inhibition was dose related. The TRH-induced prolactin release was not affected by GH-RIH. This dissociation of the thyrotrophin and prolactin responses to TRH by GH-RIH suggests that there are different mechanisms for release of thyrotrophin and prolactin and that only the former … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0
2

Year Published

1976
1976
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(14 citation statements)
references
References 15 publications
1
11
0
2
Order By: Relevance
“…The levels in craniopharyngiomas are to be contrasted with the findings in pituitary adenomas, where we and others (17) have found that the prolactin values are increased in approximately 70% of cases, often to a very high degree, and in these patients, active secretion of prolactin by the tumor itself appears to take place. The absence of any consistent relationship between the prolactin and TSH response to TRH indicates that the secreting cells have different sensitivities to TRH, and there is evidence that the release mechanisms for the two hormones are quite separate (18).…”
Section: Discussionmentioning
confidence: 98%
“…The levels in craniopharyngiomas are to be contrasted with the findings in pituitary adenomas, where we and others (17) have found that the prolactin values are increased in approximately 70% of cases, often to a very high degree, and in these patients, active secretion of prolactin by the tumor itself appears to take place. The absence of any consistent relationship between the prolactin and TSH response to TRH indicates that the secreting cells have different sensitivities to TRH, and there is evidence that the release mechanisms for the two hormones are quite separate (18).…”
Section: Discussionmentioning
confidence: 98%
“…It was also reported that GH may influence the TRH mediated secretion of TSH (Root et al, 1973). While somatostatin inhibited TSH secretion by TRH in normal people and in patients with primary hypothyroidism (Carr et al, 1975), the possibility of the participation of somatostatin in the regulation not only of GH but TSH serection in case of TRH administration should also be considered.…”
Section: Synopsismentioning
confidence: 99%
“…As far as growth hormone (GH) release is concerned somatostatin has, indeed, been shown to be an effective inhibitor in a number of species (rat, dog, baboon, man) independently of the agents used for stimulation of the secretion (arginine, L-dopa, barbiturates, chlorpromazine, exercise, sleep, meals, catecholamines, insulin hypoglycemia) [12,43,85,89,98,53,66,73,79,108,40,56]. This inhibitory action of somatostatin on the release of pituitary hormones seems also to include TSH [105,98,17].…”
Section: On Endocrine Functionsmentioning
confidence: 99%